Borobudur as a Symbol of Religion and Culture (Sociocultural study of Nyadran and Sedekah Bumi Traditions among Central Javanese Buddhists) - Tri Yatno (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
There are three results of this research, (a) the role of Borobudur as a symbol, Borobudur Temple is not only a Buddhist religious site but also a cultural symbol that connects spiritual values with the local culture of Javanese society. Borobudur has a broader meaning in a socio-cultural context, as a center of cultural identity that unites religion and local traditions, (b) harmony of the Nyadran and Sedekah Bumi traditions with the symbolic meaning of Borobudur. The Nyadran and Sedekah Bumi traditions are in harmony with the symbolic values of Borobudur which are reflected in the relationship between humans, nature and ancestors. Nyadran as a ritual of respect for ancestors contains moral and spiritual values that are in line with Buddhist teachings about karma and enlightenment. Likewise, Sedekah Bumi expresses gratitude towards nature, reflecting awareness of the importance of maintaining balance between humans and the environment. (c) harmonious integration between Buddhists, Buddhists and local culture. The tradition of Nyadran and Sedekah Bumi carried out by Buddhists in Central Java shows a harmonious integration between Buddhist teachings and local culture, thus making Borobudur a symbol of social cohesion and diversity. These two traditions have experienced cultural adaptation to become post-traditions. namely maintaining the tradition of Nyadran and Sedekah Bumi to the earth in the modern era accompanied by entertainment, but still maintaining its core meaning